SWITCHING CODES IN THE “CONVEYING MESSAGE” PATTERN OF TEACHER’S COMMUNICATION - Budiartha, Christianus I Wayan Eka; Marenthina, Marenthina (ELTR Journal, 2026)
Most Indonesian people can speak at least two languages, i.e., Indonesian and a local language. The fact that people can use more than one language or code in their daily communication has encouraged them to mix the codes when they speak to understand communication better. The situation in which people use two or more languages in the same sentence or discourse is known as code-switching. The main objective of this study is to analyse types of code-switching commonly used by teachers and students during online learning, particularly to identify their motivational background and to know the communication pattern in negotiating. A qualitative descriptive approach was employed through observation, interviews, and a survey to carry out this study. The data show that intra-sentential code-switching was the most dominant code used by teachers and students in the online classroom. Besides, the most predominant pattern of code-switching in conveying messages is the back-channelling signals, the bracket signals, and the turnover signals. From the patterns, teachers wanted to keep the online classroom activities engaging, active, and efficient.